PENGARUH SUMBER BELAJAR AKUNTANSI DAN INTERAKSI PEMBELAJARAN TERHADAP HASIL BELAJAR AKUNTANSI DASAR - Trisna Nurlaela Sari; Ratna Tiharita; Yopi Nisa Febianti (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2021)
This study aims to determine the significant effect of accounting learning resources and learning interactions on basic accounting learning outcomes, and to determine the simultaneous effect of accounting learning resources and learning interactions on basic accounting learning outcomes. The research approach used is a quantitative approach with a survey method. The population in this study were all students of class XII IPS SMAN 1 Cilimus Kuningan for the 2020/2021 academic year, totaling 202 students. The sample technique used is simple random sampling with a sample of 67 students. Data collection techniques through questionnaires and documentation, then the data were analyzed using multiple linear regression analysis. The results showed that: 1) accounting learning resources had a significant effect on basic accounting learning outcomes with a significance value of 0.005 <0.05; 2) learning interactions have a significant effect on basic accounting learning outcomes with a significance value of 0.003 < 0.05; and 3) accounting learning resources and learning interactions simultaneously affect basic accounting learning outcomes, where the calculated F value is 3.226 > F table 3.14, and the significance value is 0.046 < 0.05.